The Jews in Lombard Christian Art (14th‐15th Centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The research investigates the attitude of the Visconti and Sforza dynasties and of the Christian population living under their rule towards the Jews in the 14th and 15th centuries, using art as a primary source. The study shows that the portrayal of the Jews in Lombard artistic production reflects not only changing stylistic conventions, but also the modification of the Christian society’s disposition towards the Jews occurred during the 15th century. The worsening of the representation of the Jews parallels the increasing tensions highlighted by the documentary sources. While until beyond the mid-fourteenth century Jews, when identified iconographically, are depicted realistically, negative attributes such as the hooked nose, extravagant or exotic clothing, the moneybag and the pointed hat, become increasingly common during the fifteenth century. The analysis of the iconography also revealed how the debasement of the image of the Jews preceded, within the ducal patronage, the tightening of regulations against Jews residing in the Milanese domains. Cultural change, even within the ducal court, is thus manifested in advance of political change.
Keywords: Jews; Visconti; Sforza; Anti-Judaism; late Middle Ages